Long-term neurological intact survival and quality of life after refractory out-of-hospital cardiac arrest treated with rescue mechanical circulatory support. (3rd October 2022) - Rasalingam Moerk, S; Kristensen, L Q; Osterlund, L G; Christensen, S; Tang, M; Terkelsen, C J; Eiskjaer, H
Abstract: Background: Mechanical circulatory support (MCS) with either veno-arterial extracorporeal membrane oxygenation (V-A ECMO) or Impella has emerged as a rescue therapy for refractory out-of-hospital cardiac arrest (OHCA). However, only short-term outcome is specified and most studies do not report follow-up beyond six months. Long-term survival and quality of life in this high-risk population remains unknown. Purpose: To determine long-term neurological intact survival and quality of life in patients with refractory OHCA treated with MCS. Methods: This was an observational, single-centre study of OHCA-patients from January 2015 to December 2019. Patients treated with MCS for OHCA were compared with patients receiving conventional cardiopulmonary resuscitation (CPR). A follow-up of long-term survivors in the MCS group was conducted (>1 year after arrest). This included health related quality of life questionaries (Short Form-36 [SF-36]) and assessment of neurological function with Cerebral Performance Category (CPC). Good neurological outcome was defined as CPC 1 and CPC 2. Results: A total of 1015 with OHCA were included; 101 received MCS for refractory cardiac arrest. Among these V-A ECMO was deployed in 97 patients and Impella in 4 patients. The MCS group had significantly longer low-flow times compared to the conventional group (105 [IQR, 94–123] minutes versus 18 [IQR 10–39] minutes) and were more metabolically deranged upon arrival at hospital (Table 1). In patients receiving MCS, the hospital discharge rate was 27% and good neurological outcome was seen in 93% among patients discharged. At follow-up, 15 out of 21 long-term survivors participated. Median follow-up time was 4.8±1.6 (range 2.8–6.1 years). Mean age at follow-up was 61±7.3 years, 11 (73%) were men. Neurological outcome with CPC 1 was found in 12 patients (80%), with CPC 2 in 2 patients (13%), and with CPC 3 in 1 patient (7%). Two had improved neurological status from CPC 2 to CPC 1 since discharge. Mean scores of the SF-36 revealed an overall high level of psychical and mental health in long-term survivors (Figure 1). Conclusion: Long-term survival with good neurological outcome was high in patients with refractory OHCA treated with MCS despite prolonged resuscitation and severe metabolic derangement. These patients may expect a reasonable quality of life after discharge. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Department of Cardiology, Aarhus University HospitalSnedkermester Sophus Jacobsen og hustru Astrid Jacobsens Fond